2020
DOI: 10.29080/ipr.v2i2.246
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Self-Control on Cheating Among Indonesian College Students

Abstract: Cheating among college students has long been a concern in the academic field. In addressing this problem, it is imperative to determine in what circumstances college students cheat. Looking into the internal factor, previous research found that the depletion of self-control increased the probability of cheating. To determine whether this result could be replicated in an Indonesian population, we conducted an experimental study. A sample of 63 undergraduates was randomized into two groups, a self-control deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…sedangkan laki-laki seringkali abai terhadap kepatuhan penerapan pencegahan COVID-19 sehingga di lapangan, pasien laki-laki cenderung lebih banyak dibanding pasien perempuan. Hal ini tidak sesuai dengan penelitian (Ednadita et al 2020) yang menyatakan tidak ada perbedaan signifikan antara jenis kelamin terhadap self control dalam hal ini kepatuhan. Penelitian tersebut juga mengungkapkan bahwa kerentanan dan kematian COVID-19 amat berbeda jika dilihat dari perspektif gender, diluar variabel perbedaan genetik dan imunologi, ada tidaknya komorbid, perilaku dan pekerjaan.…”
Section: Tabel 1 Karakteristik Respondenunclassified
“…sedangkan laki-laki seringkali abai terhadap kepatuhan penerapan pencegahan COVID-19 sehingga di lapangan, pasien laki-laki cenderung lebih banyak dibanding pasien perempuan. Hal ini tidak sesuai dengan penelitian (Ednadita et al 2020) yang menyatakan tidak ada perbedaan signifikan antara jenis kelamin terhadap self control dalam hal ini kepatuhan. Penelitian tersebut juga mengungkapkan bahwa kerentanan dan kematian COVID-19 amat berbeda jika dilihat dari perspektif gender, diluar variabel perbedaan genetik dan imunologi, ada tidaknya komorbid, perilaku dan pekerjaan.…”
Section: Tabel 1 Karakteristik Respondenunclassified
“…Most students cheat to reduce the effort required to complete assignments and exams (Winardi et al, 2017). Ednadita et al (2020) also found that cheating is a common form of academic cheating among students. Cheating occurs due to the low self-control possessed by students, causing impulsive actions without thinking about the risks of their actions first (Ednadita et al, 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Even in "classical" examination system by doing test onsite, under observation from the teacher, some students often find such a way to cheat. This problem already existed at various level of education, as explained in [1], [2] and [3], and it becomes worse in online learning because take-home exams format gives them more room to cheat and/or work together with other students. All exams should be done independently, but not many students doing so in take-home exams.…”
Section: Introductionmentioning
confidence: 99%